1989
DOI: 10.1007/bf00247894
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitters, neuropeptides and binding sites in the rat mediobasal hypothalamus: effects of monosodium glutamate (MSG) lesions

Abstract: Indirect immunofluorescence histochemistry and receptor autoradiography were used to study the localization of transmitter-/peptide-containing neurons and peptide binding sites in the mediobasal hypothalamus in normal rats and in rats treated neonatally with repeated doses of the neurotoxin monosodium-glutamate (MSG). In the arcuate nucleus, the results showed a virtually complete loss of cell bodies containing immunoreactivity for growth hormone-releasing factor (GRF), galanin (GAL), dynorphin (DYN), enkephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
98
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 177 publications
(105 citation statements)
references
References 119 publications
7
98
0
Order By: Relevance
“…Not only is the arcuate nucleus the source of much of the NPY containing innervation of the PVN, but these neurons also send collaterals back into the arcuate, thereby contributing significantly to the NPY innervation of the arcuate itself (Meister et al, 1989). Regulation of the activity of these neurons may be an important way of regulating food intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only is the arcuate nucleus the source of much of the NPY containing innervation of the PVN, but these neurons also send collaterals back into the arcuate, thereby contributing significantly to the NPY innervation of the arcuate itself (Meister et al, 1989). Regulation of the activity of these neurons may be an important way of regulating food intake.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that NPY-containing neurons, which project from the arcuate nucleus to the paraventricular nucleus and also send collaterals back into the arcuate, may normally play an important role in the control of feeding behavior and in neuroendocrine regulation (Meister et al, 1989;Erickson et al, 1996a,b;Kalra and Kalra, 1996;Miller and Bell, 1996). These neurons may participate in a negative feedback "lipostat" arrangement whereby they are inhibited by leptin, a cytokine secreted from adipose tissue that inhibits food intake (Stephens et al, 1995;Erickson et al, 1996a,b;Glaum et al, 1996;Miller and Bell, 1996).…”
Section: Abstract: Neuropeptide Y; Neuropeptide Y Receptors; Arcuatementioning
confidence: 99%
“…If so, AGRP staining could be used to map the terminal projections of arcuate NPY neurons. To further ascertain the arcuate origin of AGRPimmunoreactive (ir) terminals, we also analyzed mice treated neonatally with monosodium glutamate (MSG), which induces necrosis of arcuate neurons (18), including the NPY cells (11,19). In addition, we studied AGRP in the mutant anorexia (anx͞anx) mouse, where abnormalities in arcuate NPY histochemistry have been demonstrated (9).…”
mentioning
confidence: 99%
“…In genetic models of feeding disorders, arcuate NPY overexpression has been linked to hyperphagia and obesity (8), and NPY deficiency has been linked to hypophagia and anorexia (9). However, surprisingly little information is available on the arcuate NPY projections, and targets for these neurons so far have been demonstrated only in a limited number of hypothalamic nuclei (10)(11)(12). Recently, Hahn et al (13) and we (14) have reported that many NPY neurons in the rodent arcuate coexpress agouti gene-related protein (AGRP) (15), an endogenous antagonist of the anorexigenic melanocortin peptides, e.g., ␣-melanocytestimulating hormone (␣MSH) (16,17).…”
mentioning
confidence: 99%
“…36, 68). For example, hypothalamic NPY systems are not essential for the mediation of exogenous NPY-induced feeding, as NPY-related lesions of the ARC, paraventricular nucleus, or basal hypothalamus fail to prevent either hyperphagic responses to ICV NPY (2,17,52,54) or the attainment of normal levels of food intake, body weight, and adiposity in adulthood (13,38).…”
Section: Sites Of Npy and Mch Actionmentioning
confidence: 99%